2022
DOI: 10.1002/slct.202200638
|View full text |Cite
|
Sign up to set email alerts
|

Weaving Hyper‐crosslinked Polymer from Alkaline Lignin for Adsorption of Organic Dyes from Wastewater

Abstract: Lignin is widely found in nature and attracts increasing concern as the renewable carbon material. In this work, hyper-crosslinked lignin was successfully prepared and applied for adsorbing dyes such as rhodamine B (RhB), methylene blue (MB) and Congo Red (CR) in wastewater. The characteristics of the alkaline lignin and hyper-crosslinked lignin were identified by Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and N 2 adsorption and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The data indicated that the q e obtained by using the pseudo-second-order kinetic model was closer to the actual data, and the R 2 obtained from the pseudo-second-order kinetic model was higher than that obtained from the pseudo-first-order kinetic model. Therefore, the adsorption kinetics of MO and MB were more consistent with the pseudo-second-order model, which indicated that the adsorption processes of MO and MB were mainly determined by the chemisorption mechanism. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data indicated that the q e obtained by using the pseudo-second-order kinetic model was closer to the actual data, and the R 2 obtained from the pseudo-second-order kinetic model was higher than that obtained from the pseudo-first-order kinetic model. Therefore, the adsorption kinetics of MO and MB were more consistent with the pseudo-second-order model, which indicated that the adsorption processes of MO and MB were mainly determined by the chemisorption mechanism. , …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the adsorption kinetics of MO and MB were more consistent with the pseudo-second-order model, which indicated that the adsorption processes of MO and MB were mainly determined by the chemisorption mechanism. 49 , 50 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four-step knitting is a whole lot more complicated than two-step knitting in that the yarns are only knitting yarns and no spool yarns [28]. A knitting cycle of the four-step method is divided into four steps, and each step of the yarn-carrier movement can only be stepped along the transverse or longitudinal direction respectively:…”
Section: Four-step Knitting Methodsmentioning
confidence: 99%